Edukasi Terapi Bermain Puzzle pada Anak Hospitalisasi di RS Awal Bros Batam - Indah Purnamasari; Julia Hermalina; Melidiya Anggun Sapitri (Lembaga Pengembangan Kinerja Dosen, 2026)
Hospitalization often triggers anxiety in children because of unfamiliar environments, invasive procedures, and disruption of daily routines. Pediatric nurses are expected to implement atraumatic care through developmentally appropriate, non‑pharmacological interventions. This community service program aimed to strengthen nurses’ and families’ skills in delivering puzzle‑based play therapy and to evaluate short‑term changes in children’s anxiety responses in the pediatric ward of Awal Bros Hospital, Batam. The program was conducted in December 2025 using an action-based approach: coordination with the ward team, preparation of graded puzzle sets and education media, bedside education for parents, and supervised play sessions. Four hospitalized children with different diagnoses (chemotherapy, childhood‑onset lupus erythematosus, febrile illness, and stoma care) participated. Anxiety was assessed before and after the session using an observation sheet and a faces anxiety scale adapted for clinical use. After a 20–30 minute session adjusted to the child’s developmental stage, all participants demonstrated lower anxiety scores and better cooperative behaviors. Caregivers also reported increased understanding of play therapy as part of holistic nursing care. Puzzle play therapy is feasible, low‑cost, and can be integrated into routine pediatric nursing to support coping during hospitalization.